15th Aeroacoustics Conference 1993
DOI: 10.2514/6.1993-4397
|View full text |Cite
|
Sign up to set email alerts
|

Shear layer resonance over open cavities at angles to the flow direction

Abstract: In the present study, self-sustained shear layer oscillations over shallow, open cavities beneath a low speed, subsonic, laminar boundary layer were studied experimentally in a wind tunnel. The cavities were rectangular in cross-section. The research concentrated upon determining the effects upon cavity resonance of rotating the leading edge of the cavity away from normal to the flow direction. Cavity resonance was identified through spectra of flow fluctuations sensed with hot wire anemometer probes. The reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Savory [10] showed that the most asymmetric flow pattern inside a cavity and the lowest drag occur at = 45 ∘ for L/H = 6-16. In terms of self-sustained oscillations, Bari and Chambers ( ∞ = 20-44 m/s) [11] showed that the yaw angle for a cavity need not significantly affect the resonant frequencies. However, there may be a switch in the dominant mode and the effective stream-wise length, / cos( ), of a cavity at yaw is probably not a suitable characteristic length.…”
Section: Introductionmentioning
confidence: 99%
“…Savory [10] showed that the most asymmetric flow pattern inside a cavity and the lowest drag occur at = 45 ∘ for L/H = 6-16. In terms of self-sustained oscillations, Bari and Chambers ( ∞ = 20-44 m/s) [11] showed that the yaw angle for a cavity need not significantly affect the resonant frequencies. However, there may be a switch in the dominant mode and the effective stream-wise length, / cos( ), of a cavity at yaw is probably not a suitable characteristic length.…”
Section: Introductionmentioning
confidence: 99%